Implementasi Penerima Dana Santunan Yayasan Menggunakan Metode SAW (Studi Kasus: Yayasan Mdta Nurul Ikhwan) - Aria Satria (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2021)
The use of a Decision Support System (DSS) can assist a person in making accurate and targeted decisions. Many problems can be solved by using SPK, one of which is to analyze the recipients of the foundation's annual period of compensation. The method that can be used for this Decision Support System is to use Simple Additive Weighting (SAW). In determining the recipient of foundation compensation, there are many criteria that must be possessed by individuals as a condition for obtaining foundation compensation. Foundations must have criteria to determine who will be selected to receive foundation compensation for the annual period with the aim of helping someone who is underprivileged or excels during their studies. In this study, a case will be raised, namely looking for the best alternative based on the criteria determined by the foundation using the SAW (Simple Additive Weighting) method. The research was conducted by finding the weight value for each attribute, then a ranking process was carried out which would determine the optimal alternative, namely the right student to receive foundation compensation.